Implementation of the GASING Approach Integrated with the STAD Model in Teaching Integer Operations through Local Wisdom - Nerru Pranuta Murnaka; Haryanti Haryanti; Muhammad Nur Huda; Kristining Seva; Marevic Jean P. Lutog (Jurnal Ilmiah Pendidikan Dasar, 2026)
The relatively low numeracy achievement of Indonesian students in national and international assessments highlights the need for more innovative and student-centred mathematics instruction. Learning activities that primarily emphasise procedural exercises often limit students’ conceptual understanding and interest in mathematics. Therefore, instructional approaches that integrate collaboration, educational games, and local cultural contexts are needed to create meaningful and enjoyable learning experiences. This study aimed to examine the implementation of the GASING Approach integrated with the Student Teams Achievement Division (STAD) model and local wisdom-based games in improving students’ learning outcomes on integer arithmetic operations. This study employed a quantitative approach using a pre-experimental method with a One-Group Pretest–Posttest Design. The participants were 28 fifth-grade students of SD Tlogosari Kulon 05. Data were collected through pretest and posttest instruments covering addition, subtraction, multiplication, and division of integers. The data were analysed using descriptive statistics and the Normalised Gain (N-Gain) test. The findings showed an improvement in students’ mathematics learning outcomes after the intervention. The mean pretest score increased from 50.54 to 84.61 on the posttest. Learning mastery improved from 0% to 75%, while the average N-Gain score was 0.689, indicating a medium level of improvement. These results suggest that the implemented learning approach effectively enhanced students’ understanding of integer arithmetic operations. The integration of the GASING Approach, the STAD model, and local wisdom-based games created an enjoyable, collaborative, and meaningful learning environment that supported the improvement of elementary students’ mathematics achievement in integer arithmetic operations.